Frontiers of the Roman Empire = Frontières de l'Empire Romain - Breeze, David J. (Archaeopress Archaeology, 2022)
The North Sea and Channel coasts form the geographic frontier of the Roman Empire with the sea - the edge of the then known world. This border represents a page in military maritime history, but its coasts, in Great Britain, the Netherlands, Belgium and France, contain archaeological sites of high heritage value that deserve a large audience.